Combatting occupational deprivation and advancing occupational justice in institutional settings: Using a practice-based enquiry approach for service transformation. (January 2020) - Whiteford, Gail; Jones, Katherine; Weekes, Gemma; Ndlovu, Nomagugu; Long, Cassandra; Perkes, Danielle; Brindle, Sophie
Introduction: Occupational deprivation is a risk for residents of institutions. This is problematic at several levels: it can cause diminution of individual capacities; such environments pose philosophical and practical challenges for occupational therapists and the erosion of human rights can be an issue. Occupational therapists in an Australian forensic mental health setting 'reclaimed' occupation-centred practice, committed to occupational justice and tackled the experience of occupational deprivation of patients through utilising a practice-based enquiry approach. Method: A community of practice scholars used a practice-based enquiry approach – a type of action methods research – involving iterative cycles of data collection, analysis, critique and implementation of practice innovations. Findings: Through the practice-based enquiry process, participants' practice became more occupation-centred, based and focused, resulting in: the creation of more opportunities for patients, which combatted occupational deprivation and increased potential for community reintegration; enhanced professional satisfaction and identity; and increased institutional 'valuing' of the occupational therapy service. Conclusion: Ameliorating occupational deprivation can be achieved through becoming occupation-centred and embracing a stated commitment to occupational justice in the challenging practice setting of a forensic hospital. The use of the deeply reflective process of practice-based enquiry was pivotal to this shift in focus for the group of occupational therapists who participated in this study and also contributed to enhanced practitioner satisfaction, identity, autonomy and confidence.